Technology aspect of Electric Vehicles Initiative's social sustainability. Issue 1 (23rd November 2021) - Tyagi, Ruchi; Vishwakarma, Suresh
Abstract : Purpose: The Electric Vehicles Initiative (EVI) is a multi-government policy forum devoted to speed up the introduction and adoption of electric vehicles (EVs) worldwide. EVI key themes for sustainable development include energy-efficient transportation with e-mobility (drive-by science and technology), reduced greenhouse gas emissions, decreased oil dependence and improved local air quality. India's transport sector contributes around 142 million tons of CO2 every year, with road transport contributing 123 million tons. Design/methodology/approach: Review methodology forms a basis for knowledge development, creating guidelines for policy and practice. Quality assessment of review articles is by using mixed methods appraisal tool (MMAT). Findings: The research trends on Sustainable Development Goal (SDG) technological and social aspects highlight the critical role of technology in economic and social development, emphasising infrastructure development and communication of government policy and rewards for awareness and end-user acceptance. Originality/value: The scenario brings a school of thought if it is equally important to address a social perspective to improve India's perception and acceptance of technology-enabled EVs.